The dead and the dying a criminal edition - Brubaker, Ed (Criminal, 2008)
"A boxer trying to escape his father?s shadow and find a life outside the world of crime where he was raised. A Vietnam vet comes home to find the things he learned in the service are both a blessing and curse. An innocent girl turned femme fatale struggles to find a way off her path of destruction -- P. [4] of cover.